TINGKAT RESILIENSI RUMAH TANGGA PETANI PADI SAWAH DALAM MENGHADAPI BENCANA BANJIR - Samuel Lantip Wicaksono; Lies Sulistyowati; Trisna Insan Noor (Universitas Galuh, 2023)
The Citanduy Watershed is the key to the distribution of water to the surrounding area. Watershed functions that are not good will result in floods and droughts. Padaherang District is one of the districts affected by flooding, especially for lowland rice farming households. Repeated flooding causes farmers to have resilience. This study aims to analyze the level of resilience of farmer households to flood disasters. The method used is a mixed method with a sample size of 120 farmer households. The level of household resilience of lowland rice farmers is in the high category. This is evidenced by an unyielding attitude and a desire to change things for the better with enthusiasm and confidence.